Hsa_circ_0062270 Promotes Tumorigenesis of Melanoma by Stabilizing the Linear Transcript Cell Division Cycle Protein 45 - Wei, Cuie; Sun, Wentao; Liu, Changhai; Meng, Fanjun; Sun, Lele; Ding, Xiangsheng (Frontiers in Genetics, 2022)
Background: To elucidate the potential biological function of hsa_circ_0062270 in the malignant process of melanoma and the molecular mechanism. Methods: Quantitative real-time polymerase chain reaction (qRT-PCR) was conducted to examine relative level of hsa_circ_0062270 in melanoma tissues and normal skin tissues. The diagnostic and prognostic potentials of hsa_circ_0062270 in melanoma were evaluated. The regulatory effect of hsa_circ_0062270 on the expression of linear transcript CDC45 was also examined. Results: hsa_circ_0062270 was up-regulated in melanoma samples and cell lines, which displayed certain diagnostic and prognostic potentials in melanoma. Inhibition of hsa_circ_0062270 attenuated the proliferative, migratory and invasive functions. hsa_circ_0062270 could stabilize the expression of linear transcript CDC45, and thus participated in the malignant process of melanoma. Conclusions: hsa_circ_0062270 promotes proliferative, migratory and invasive functions of melanoma cells via stabilizing the linear transcript CDC45. hsa_circ_0062270 can be used to diagnosis and treatment of melanoma.